Comparison of the Effect on Vessel Density and RNFL between Carteolol and Latanoprost - Nutterova, Elena; Fus, Martin; Bartosova, Libuse; Klimesova, Iva; Lestak, Jan (Journal of clinical medicine, 2022)
The aim of the study was to compare the treatment of hypertensive glaucoma (HTG) in the early stages with carteolol and latanoprost by assessing the change in vessel density (VD) and retinal nerve fibre layer (RNFL). Methods: The first group with diagnosed HTG consisted of 46 eyes treated with carteolol; the second group consisted of 52 eyes treated with latanoprost. The following examinations were evaluated in all patients: intraocular pressure (IOP), retinal nerve fibre layer (RNFL), vessel density (VD) and visual field examination (glaucoma fast threshold test). The results were compared before treatment and 3 months after treatment. Results: There was no difference in the overall visual field defect (OD) between groups before treatment. After treatment, there was a decrease in IOP in both groups (carteolol-treated group had a mean decrease of 5.8 mmHg and latanoprost-treated eyes had a mean decrease of 7 mmHg). This difference was not statistically significant (p = 0.133). No similar difference was observed for RNFL (p = 0.161). In contrast, the change in the VD parameter was statistically significant between groups (p < 0.05), with a greater difference observed in the carteolol-treated group of eyes. Carteolol had a better effect on the VD.
Keywords: RNFL; OCTA; vessel density; treatment with carteolol and latanoprost; hypertensive glaucoma